How Can Unmanned Aerial Vehicles Be Used for Detecting Weeds in Agricultural Fields? - Nur Adibah Mohidem; Nik Norasma Che’Ya; Abdul Shukor Juraimi; Wan Fazilah Fazlil Ilahi; Muhammad Huzaifah Mohd Roslim; Nursyazyla Sulaiman; Mohammadmehdi Saberioon; Nisfariza Mohd Noor (Multidisciplinary Digital Publishing Institute, 2024)
Agriculture 2021, 11(10), 1004